2011 Irish Machine Vision and Image Processing Conference 2011
DOI: 10.1109/imvip.2011.19
|View full text |Cite
|
Sign up to set email alerts
|

A Texture Analysis Approach to Identifying Sabellaria Spinulosa Colonies in Sidescan Sonar Imagery

Abstract: Offshore wind farms are undergoing unprecedented development as EU member states focus on complying with 2020 renewable energy mandates. However, wind farm site placement requires great care, to avoid compromising protected habitats, such as Sabellaria spinulosa reefs. This paper presents an investigation into the potential of different feature generation methods for identifying sidescan sonar image textures characteristic of Sabellaria spinulosa colonies. We propose an extensible test methodology and carry ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…18 For an evaluation of several state-of-the-art statistical, signal processing-based and morphologybased features applied to a related problem on sonar waterfall imagery, refer to our recent paper. 13 Since GLCM features are probably the most widely used in the domain, we apply them in our test cases.…”
Section: Application Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…18 For an evaluation of several state-of-the-art statistical, signal processing-based and morphologybased features applied to a related problem on sonar waterfall imagery, refer to our recent paper. 13 Since GLCM features are probably the most widely used in the domain, we apply them in our test cases.…”
Section: Application Contextmentioning
confidence: 99%
“…45,50 Of particular concern are protected habitats, such as reefs formed by colonies of the tube-building worm, Sabellaria spinulosa (Sabellaria). 13,51,52 In our test cases, we focus on Sabellaria as the target texture in sonar mosaic imagery e Directionally dependent features can be useful for discriminating anisotropic textures but this is not of concern here. and attempt to discriminate it from other specific seabed types.…”
Section: Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Although both first -order statistical texture and second-order statistical texture analysis have been proven as promising input for image segmentation and classification, most studies tend to use second-order analysis. A popular subject of research in sidescan sonar image analysis that can be found in several studies is use of the Grey Level Co-occurrence Matrix (GLCM) method to extract the second-order texture features (Lianantonakis & Petillot, 2007;Harrison et al, 2011;Hamilton, 2015;Buscombe, 2017;Hamill et al, 2018). Blondel et al, (1998) demonstrated GLCM s could be successfully used to segment SSS images.…”
mentioning
confidence: 99%